Why the poor have many children - Edita A. Tan; Katrina Dinglasan (University of the Philippines, School of Economics (UPSE), 2012)
This is a follow up note on the UP School of Economics Faculty paper on the population issue. The poor who belong to the lowest two deciles of the income distribution have much higher actual and desired number of children, respectively 5.2 and 3.5. In contrast, the upper middle and higher income groups have less than 3 children which equal their desired number. It is argued that the poor who suffer serious deprivation in basic needs and see little opportunity for their children's education and other opportunities feel little interest in controlling their family size. For them it would not matter how many children they may bear since the intensity of their poverty as measured by average income to poverty ratio and food consumption to subsistence ratio marginally improve as the number of children falls. It is suggested that for a family planning program to succeed, it must be part of an anti poverty strategy.
Keywords: 330; Armut; Fertilität; Familienplanung; Soziale Lage; Philippinen